2015
DOI: 10.4103/0019-5049.153039
|View full text |Cite
|
Sign up to set email alerts
|

Interscalene brachial plexus block for shoulder arthroscopic surgery: Prospective randomised controlled study of effects of 0.5% ropivacaine and 0.5% ropivacaine with dexamethasone

Abstract: Background and Aims:Various adjuvants have been used to prolong the duration of local anaesthetic action after peripheral and regional nerve blocks. We evaluated the effect of dexamethasone on the duration of pain relief in shoulder arthroscopic surgeries performed under interscalene brachial plexus using ropivacaine as local anaesthetic.Methods:After Ethical Committee approval and informed consent from patients we performed a prospective, randomised, comparative study on patients scheduled for arthroscopic sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…The addition of dexamethasone to regional anesthetics such as lidocaine, bupivacaine, and other sodium channelblocking anesthetics has been shown to prolong the duration of analgesia. 5,11,[32][33][34][35][36][37] Recently, a meta-analysis of nine randomized trials by Choi et al 1 found that the addition of dexamethasone to regional anesthetics prolongs the duration of analgesia by approximately six hours. Furthermore, they reported a trend towards decreased opioid consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of dexamethasone to regional anesthetics such as lidocaine, bupivacaine, and other sodium channelblocking anesthetics has been shown to prolong the duration of analgesia. 5,11,[32][33][34][35][36][37] Recently, a meta-analysis of nine randomized trials by Choi et al 1 found that the addition of dexamethasone to regional anesthetics prolongs the duration of analgesia by approximately six hours. Furthermore, they reported a trend towards decreased opioid consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the cesarean section rate was 24.24% in the levobupivacaine group, which validates the above point of view. Ropivacaine is less toxic to the heart than levobupivacaine, and it has a lighter neuromotor block effect (25). Combined spinal-epidural anesthesia with ropivacaine has a lesser influence on the cervical and vaginal motor nerves in the lower uterine segment, which decreases the birth canal resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Both EA and GA can prevent the pain but EA also can maintain the function of motor of lower limbs which is called sensory-motor separation. 17 Currently, the use of EA is comparatively infrequent. Ropivacaine has a stronger ability to inhibit nerve conduction in pain sensing fibers and low concentration medications can preserve motor function and only blocks sensation during surgery.…”
Section: The Concentration Of Ropivacaine In Eamentioning
confidence: 99%